Low-temperature Interconnection of PVD-Aluminium Metallization. (November 2016) - Geipel, Torsten; Kumm, Julia; Moeller, Monja; Kroely, Laurent; Kraft, Achim; Eitner, Ulrich; Wolf, Andreas; Zhang, Zhenhao; Wohlfahrt, Peter
Abstract: Aluminium, thermally evaporated with physical vapor deposition (PVD), is considered a cost efficient rear metallization for crystalline silicon heterojunction or tunnel oxide passivated solar cells. Owing to the temperature-sensitivity of the solar cell structure, potential routes of low temperature interconnection methods for PV module integration are assessed. Textured wafers with a full area 2 μm PVD-Al metallization are divided into two groups: The first is capped with sputtered 100 nm Ti and 400 nm Ag for testing solderability. The second is capped with 400 nm Ag for electrically conductive adhesive (ECA) interconnection. Low temperature soldering with Sn43Bi57 and Sn41Bi57Ag2 coated ribbons and ribbon interconnection with two ECAs are evaluated in terms of peel strength, contact resistivity and accelerated aging properties. It is found that peel strength of soldered interconnections on the Al/Ti/Ag achieve between 1.5 N mm -1 to 2 N mm -1 whereas glued interconnections on Al/Ag between 0.5 N mm -1 to 1 N mm -1 . The contact resistivity is 2.6 × 10 -3 mΩ cm2 to 3.6 × 10 -1 mΩ cm2 for both interconnection technologies. Soldered samples show a stable contact resistivity when tested in 1000 h in damp heat conditions or 200 thermal cycles. The contact resistivity of glued interconnections increases to 1 mΩ cm2 to 10 mΩ cm2 along with an observed disintegration of the Al-layer and an ablation of the Ag-capping from the Al-layer.